Electron microscopy study of lizard spermiogenesis in Tropidurus torquatus (Lacertilia) - Da Cruz Landim, C.; Da Cruz Hofling, M. A. (Firenze University Press, 1977)
In the course of an investigation on lizard spermiogenesis, the authors have observed events connected with the differentiation of the acrosome and middle-piece of the spermatozoa. Some differences from other reptilians were found as well as: the presence of a subacrosomal space, the absence of the fibrous sheath in the middle-piece, and a very short neck in the mature spermatozoa.
Keywords: acrosome; amphibia; electron microscopy; spermatogenesis; spermatozoon; theoretical study